2018
DOI: 10.18632/oncotarget.24087
|View full text |Cite
|
Sign up to set email alerts
|

The modified glasgow prognostic score is an independent prognostic indicator in neoadjuvantly treated adenocarcinoma of the esophagogastric junction

Abstract: The modified Glasgow Prognostic Score (mGPS) combines the indicators of decreased plasma albumin and elevated CRP. In a number of malignancies, elevated mGPS is associated with poor survival. Aim of this study was to investigate the prognostic role of mGPS in patients with neoadjuvantly treated adenocarcinomas of the esophagogastric junction 256 patients from a prospective database undergoing surgical resection after neoadjuvant treatment between 2003 and 2014 were evaluated. mGPS was scored as 0, 1, or 2 base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 33 publications
2
29
0
Order By: Relevance
“…Recently, several common inflammation‐based prognostic scores, including the NLR, PLR, GPS, and CONUT score have been reported to have prognostic value in patients with various types of cancers . These biomarkers can be evaluated easily by sampling a small amount of peripheral blood.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, several common inflammation‐based prognostic scores, including the NLR, PLR, GPS, and CONUT score have been reported to have prognostic value in patients with various types of cancers . These biomarkers can be evaluated easily by sampling a small amount of peripheral blood.…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing data that malnutrition, skeletal muscle loss, and a systemic inflammatory response are associated with poor outcomes in patients suffering from various types of cancers . We previously reported that skeletal muscle loss was strongly associated with a poor long‐term prognosis in patients who underwent surgical treatment of AEG and UGC .…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations